Communicative resources and credibility in public discourse on refugees. (23rd April 2019) - Smith-Khan, Laura
Abstract: This article examines how communicative resources affect the construction of credible texts and identities in a public debate on Australia's treatment of a refugee. It centres on two key written statements—one from the Immigration Minister, and another from a Somali refugee. The analysis is divided into four levels, exploring the parties' respective linguistic, material, identity, and platform resources, and how these impact their statements' creation and reception, and their participation in discourse creation more generally. The article finds that there are inequalities on all four resource levels that largely undermine the refugee's ability to present a credible text and identity and challenge mainstream discourse on refugees. The article demonstrates how a multi-level analysis of communicative resources can challenge assumptions about participation and uncover inequalities invisible in the prevailing discourse. (Asylum, Australia, communicative resources, discourse, intercultural communication, media, power, refugee)*